KONTRIBUSI BISNIS PADA TATA KELOLA PENDIDIKAN DI PONDOK PESANTREN SUNAN DRAJAT, LAMONGAN - Sulanam Sulanam; Qomariya Rahma Ayu (STKIP Pesisir Selatan, 2026)
Apart from being a source of independent funding, these business activities also play an important role in improving educational governance within the Sunan Drajat Islamic Boarding School environment. This study aims to examine the contribution of business activities to educational governance at Pondok Pesantren Sunan Drajat (PPSD) Lamongan. The research uses a qualitative approach with a descriptive method. Data were collected through interviews, observations, and documentation involving the pesantren’s leaders, business managers, teachers, and students. The results show that business activities developed by the pesantren, such as BMT and Toserba Sunan Drajat, have a significant impact on the sustainability and improvement of education within the institution. These business units not only serve as financial support but also contribute to improving educational facilities, strengthening management systems, and instilling Islamic entrepreneurial values among students. The established economic independence enables the pesantren to manage education more professionally and sustainably without relying on external assistance. The integration of business and education at PPSD serves as a model for Islamic educational institutions that can adapt to modern developments while maintaining Islamic and social values.